WATER BALANCE IN 51C PLOT OF PROTECTED FOREST AREA, RPH CISURUPAN, BKPH BAYONGBONG, KPH GARUT, WEST JAVA REGIONAL DIVISION PERUM PERHUTANI - LUH PUTU SUSANTI DEWI (NIM : 11513012), NI
Most of the protected forest area has changed its function to become an agricultural area based on meeting the economic needs of the community around the forest area. This change has an impact on reducing the quantity of groundwater and the potential for natural disasters such as floods and droughts. The purpose of this research was to determine the surplus (deficit) of groundwater and the drought index from the impact of changes in vegetation cover. Then vegetation analysis is needed to determine the vegetation conditions that have the most equitable hydrological conditions. The calculation of the water balance was carried out in 51C Plot of Protected Forest Area, RPH Cisurupan, BKPH Bayongbong, KPH Garut, West Java Regional Division Perum Perhutani on three blocks namely mixed forest block, agricultural block, and open area based on the vegetation cover conditions. The water balance calculation method used is the Thronthwaite-Mather method. Rainfall in the three blocks is 1527.27 mm / year. The results showed that the actual evapotranspiration values on open area, agricultural blocks, and mixed forest blocks intervened sequentially which amounted to 744.13 mm / year, 44.65 mm / year, and 745.69 mm / year. The three blocks experienced groundwater deficits from July to September, while in other months there was a surplus of groundwater. Drought index in the three locations, namely in the open area block of 4.23%, in agricultural blocks 4.17%, and in mixed forest 4.03%. Runoff values for open area, agricultural blocks and mixed forest in sequence are 697.70 mm / year, 697.79 mm / year, and 697.72 mm / year. The most balanced water balance with the highest quantity of groundwater is the mixed forest because it has a balanced surplus and devisit water value and the smallest drought index. Vegetation analysis was carried out using a multilevel plot method. From the results of vegetation analysis, mixed jungle blocks have the highest tree-level vegetation dominance with the Toona sureni type which has the highest importance value index (IVI) of 103.74%.